A position- and time-dependent pressure profile to model viscoelastic mechanical behavior of the brain tissue due to tumor growth. Issue 6 (26th April 2023) - Abdolkarimzadeh, Fatemeh; Ashory, Mohammad Reza; Ghasemi-Ghalebahman, Ahmad; Karimi, Alireza
Abstract: This study proposed a computational framework to calculate the resultant position- and time-dependent pressure profile on the brain tissue due to tumor growth. A finite element (FE) patch of the brain tissue was constructed and an inverse dynamic FE-optimization algorithm was used to calculate its viscoelastic mechanical properties under compressive uniaxial loading. Two patient-specific post-tumor resection FE models were input to the FE-optimization algorithm to calculate the optimized 3 rd -order position-dependent and normal distribution time-dependent pressure profile parameters. The optimized viscoelastic material properties, the most suitable simulation time, and the optimized 3 rd -order position- and -time-dependent pressure profiles were calculated.